Lexical meaning and cultural meaning in lingual units in Prajuritan dance art in Semarang regency: An ethnolinguistic study - Nuryati, Sri; Fateah, Nur (Universitas Islam Sultan Agung, 2025)
Prajuritan dance of Semarang Regency embodies profound cultural values. This study was conducted in response to the lack of research specifically examining the lingual elements of Prajuritan dance from an ethnolinguistic perspective. Although the dance contains linguistic expressions that reflect local cultural values, these have gradually been neglected due to its declining popularity within the community. This study aims to analyze the forms of lingual units in Prajuritan dance in Semarang Regency through an ethnolinguistic lens to uncover both their lexical and cultural meanings. A qualitative method was employed, utilizing an ethnographic approach. Data were collected through face-to-face interviews, audio recordings, and field notes from informants who are traditional artists in Semarang Regency. The data were then analyzed through reduction, presentation, and conclusion drawing. The findings revealed 61 lingual units in Prajuritan dance, including 21 monomorphemic words, 7 polymorphemic words, and 33 phrases. These units are classified into six categories: paraga, busana, ubarampe, accompaniment, movement, and gelar. Each unit carries not only lexical meanings but also cultural values embedded in traditional roles and expressions. Ultimately, Prajuritan dance is not merely a performing art, but a cultural repository that safeguards ancestral wisdom and must be preserved for future generations.